Determinants of inflation in Kenya and the moderating effects of governance regimes - Maonga, Solomon Atura (Strathmore University, 2022)
A high level of inflation is undesirable because it causes a depreciation of the local currency. It also makes long-term financial planning difficult for market participants resulting in an inefficiency in a market economy, and subsequently, a lower rate of economic growth. An ideal economy would have price stability (low and steady inflation) and the wider economic goal of strong and sustainable growth and employment would be achieved. This study examined monetary and non-monetary determinants of inflation in Kenya, a developing country with a monetary policy objective of inflation-targeting. Using an Error Correction Model (ECM) based on the Autoregressive Distributed Lag (ARDL) model to explain the short run and long run impacts of each variable on inflation, this study covered secondary quarterly data spanning 25 years (1996 – 2020). The unique contribution of the study was the investigation of the moderating effects of governance regimes on the determinants of inflation. Governance regimes were examined with respect to the President of the country and the Central Bank Governor. The study concluded that in the Kenyan context, inflation is primarily influenced by prevailing interest rates and the most recent rates of inflation in the short run. The non-monetary factors and other monetary factors examined do not have a long run nor short run impact on the level of inflation, but given the moderating effects of governance regimes, their influence may be felt sporadically. Global oil prices and public debt levels are emerging as major factors influencing the rate of inflation. The study emphasises the importance of good governance to ensure consistency of policy across regimes in order to maintain price stability.
A Dissertation submitted to the Strathmore University Business School in partial fulfilment of the requirements for the Degree of Master of Science (MSc) in Development Finance of Strathmore University